Water footprint of wheat under different irrigation practices at Faridkot, Punjab - SOURAV CHOUDHARY; SUDHIR KUMAR MISHRA; KULVIR SINGH; RAJ KUMAR PAL; PRABHJOT-KAUR (Journal of Agrometeorology)
Field experiments were conducted during Rabi seasons at Punjab Agricultural University, Regional Research Station, Faridkot, Punjab for 13 years (2010-11 to 2022-23) to assess the water footprint (WF) of wheat crop irrigated through different methods such as conventional surface flood (SF) during 2010-11 to 2018-19, surface drip (SD) during 2019-20 to 2020-21, and subsurface drip (SSD) during 2021-22 to 2022-23. Results elucidated that quantity of the irrigation water applied to the wheat crop ranged between 209 and 375 mm in different years. Whereas, wheat yield ranged from 3450 kg ha⁻¹ (2017-18) to 5471 kg ha⁻¹ (2021-22). Wheat crop under SF irrigation recorded higher WFtotal 0.98 to 1.57 m³ kg⁻¹. The maximum rainfall 250.3 mm received in 2014-15 resulted highest WFgreen (0.46 m³ kg⁻¹) and lowest WFblue (0.45 m³ kg⁻¹). The wheat cultivation under SD and SSD reduced the WFgrey up to 35 % and WFblue up to 35.0 – 42.8 % over SF. The higher crop yield and/or fewer water consumption both are associated with the lower WF. Therefore, for hydrological resource conservation and to ensure environmental sustainability, irrigation through SSD and SD should be promoted over the traditional SF method among the farming community.